MEMBANGUN KEUNGGULAN BERSAING BERKELANJUTAN MELALUI KAPABILITAS MODAL SOSIAL DAN KINERJA PEMASARAN PADA PENGRAJIN WINGKO BABAT DI KOTA SEMARANG - Khamimah Khamimah; Sri Suyati (Serat Acitya, 2014)
This research is to examine the factors that affect the performance marketing excellence as efforts to build sustainable compete in a craftsman wingko babat  in semarang city .We explained the purpose of research done by craftsmen wingko babat  in efforts to improve the performance marketing ?Explained how large of tripe by a craftsman wingko compete to build sustained excellence among fellow craftsman wingko babat  in semarang city explain what factors causing a craftsman wingko babat  able to compete .In this study population as an object of research is all a craftsman wingko babat in semarang city , while the sample is used as a number of respondents who mingisi kuesioner.yaitu 116 respondents craftsman wingko babat  . The method chosen to analyze data should conform to variable patterns research and will diteliti.the structural equation modelling ( SEM ) of software packages statistic amos used in model and the testing of hypotheses.Mostly educated, senior / respondents master most respondents the female sex .pada the regression coefficient variable variable positip, influential latent all Likewise to the regression coefficient konstruk each variable indicate the dimensions has the highest value. Keywords: networks, trust, commitment, performance marketing- preëminence compete sustained